Healthy Eating Index-2020 and bowel habits: a cross-sectional analysis of NHANES - Chen, Rongpeng; Fu, Zexin; Feng, Zhicheng; Xiao, Feng; Wang, Guoqiang (Frontiers in Nutrition, 2025)
BackgroundDietary habits play crucial roles in gastrointestinal health. The relationship between dietary patterns, measured using the Healthy Eating Index-2020 (HEI-2020), and bowel habits remains unclear. This study aimed to explore the associations between HEI-2020 scores and bowel habits, including fecal incontinence, diarrhea, and constipation, in adults in the US.MethodsThis cross-sectional study included 11,590 participants of the National Health and Nutrition Examination Survey. Multivariate logistic regression models were used to assess the associations adjusted for demographic, socioeconomic, and health-related covariates. Weighted quantile sum (WQS) regression was used to evaluate the combined effects of the dietary components.ResultsAnalysis of 11,590 individuals showed that higher HEI-2020 scores were negatively correlated with fecal incontinence and constipation. When treated as a continuous variable, HEI-2020 scores were associated with reduced odds of fecal incontinence (weighted adjusted OR: 0.86, 95% CI: 0.79–0.95, p = 0.004) and constipation (weighted adjusted OR: 0.78, 95% CI: 0.73–0.84, p < 0.001). In quartile analysis, the highest HEI-2020 quartile was linked to a 48% lower constipation risk compared with the lowest quartile (weighted adjusted OR: 0.52, 95% CI: 0.40–0.68, p < 0.001). Subgroup analysis indicated that higher HEI-2020 scores were more strongly associated with a reduced constipation risk in participants with sleep disorders. WQS regression revealed significant protective effects of HEI-2020 scores on fecal incontinence and constipation, but not on diarrhea.ConclusionHigher HEI-2020 scores were associated with a reduced risk of fecal incontinence and constipation. Adherence to the HEI-2020 guidelines may enhance gastrointestinal health by mitigating abnormalities in bowel habits.